Activation of mesenchymal stem cells by macrophages promotes tumor progression through immune suppressive effects - Jia, Xiao-hua (Oncotarget, 2016)
Cancer development and progression is linked to tumor-associated macrophages (TAMs). Distinct TAMs subsets perform either protective or pathogenic effects in cancer. A protective role in carcinogenesis has been described for M1 macrophages, which activate antitumor mechanisms. By comparison, TAMs isolated from solid and metastatic tumors have a suppressive M2-like phenotype, which could support multiple aspects of tumor progression. Currently, it has not been clearly understood how macrophages in tumor-associated stroma could be hijacked to support tumor growth. Mesenchymal stem cells (MSCs) actively interact with components of the innate immune system and display both anti-inflammatory and pro-inflammatory effects. Here, we tested whether MSCs could favor the tumor to escape from immunologic surveillance in the presence of M1 macrophages. We found that MSCs educated by M1 condition medium (cMSCs) possessed a greatly enhanced ability in promoting tumor growth in vivo. Examination of cytokines/chemokines showed that the cMSCs acquired a regulatory profile, which expressed high levels of iNOS and MCP1. Consistent with an elevated MCP1 expression in cMSCs, the tumor-promoting effect of the cMSCs depended on MCP1 mediated macrophage recruitment to tumor sites. Furthermore, IL-6 secreted by the cMSCs could polarize infiltrated TAMs into M2-like macrophages. Therefore, when macrophages changed into M1 pro-inflammation type in tumor microenvironment, the MSCs would act as poor sensors and switchers to accelerate tumor growth.